Perceptions of social support for weight loss among patients in primary care. Issue 6 (November 2019) - Brown, Megan M.; Arigo, Danielle; Pasko, Kristen; Gupta, Adarsh
Abstract: This study examined primary care patients' experiences with support for weight loss efforts. Adult patients ( N  = 106) were recruited through primary care clinics and completed an electronic survey pertaining to their weight loss efforts. The majority (76%) received support from their existing social network (e.g., family members, professionals); 59% had used apps and <20% had used social media for support. Findings reveal differences in satisfaction with support between men and women and between support sources, which will be useful for informing weight loss interventions in primary care.